Idol Worship: Ethnicity and Difference in Global Television - Sen, Biswarup (Global Television Formats: Understanding Television Across Borders, 2012)
The worldwide success of the Idol format may not require any explanation. We live under the ubiquitous sign of globalization; and hence it should come as no surprise that mass media— which together constitute an ecumenical vehicle of culture with an insatiable appetite for proﬁt— would generate forms (or formats) of art that travel with ease and are translatable into every context. The reception of these formats is, at one level, as unproblematic as its dissemination. To be global (and who isn’t?) is to be eagerly accepting of certain languages, technologies, discourses and styles. The craze surrounding competitive singing can then be explained as one more instance of borders proving permeable to the formulas of international popular culture. It is my argument that in order to understand the unique valence and signiﬁcance of global formats, we need to go beyond issues of production, distribution and reception, and focus instead on the phenomena that arise from their instantiation . This is so because implementing a format in a speciﬁc context has consequences that are neither written into the “program” nor purely derivable from local conditions. Let me provide an illustration. The call-in talk show has recently become a staple on Indian television. The format and content of these shows would be familiar to most Western viewers— a regular host, one or more “experts” discussing politics and culture, and a ﬁnal segment devoted to phone calls from the public.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Asie du sud (corpus analysé); Inde (corpus analysé); _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Spaces of Television: Rethinking the Public/Private Divide in Postcolonial India - Kumar, Shanti (Channeling Cultures: Television Studies from India, 2014)
This chapter critically evaluates changing definitions of ‘public’ in Indian television in relation to discourses of globalization and media privatization. It examines the debate over the nationalist agenda of public broadcasting in India in relation to the demands for alternative models of broadcasting, and the rise of private commercial satellite channels since the 1990s. It also discusses how representations of traditionally private desires of sexuality and intimacy in soap operas, reality TV shows and music television are redefining the public in India. It outlines the ways in which private desire is made visible — and thus made public — through the convergence of the television screen, the cinematic screen, the computer screen, and the mobile screen. It argues that binaries of ‘public’ versus ‘private’ force us into either/or debates even though such category systems are always-already hybrid in postcolonial societies such as India.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

The Saffron Hues of Gender and Agency on Indian Television - Chakrabarti, Santanu (Channeling Cultures: Television Studies from India, 2014)
This chapter explores the contradiction between two sets of responses to the so-called K-serials, earlier, largely condemnatory ones, and more recent, largely laudatory ones. The chapter aims to understand this contradiction and resolve it. It does so by showing how K-serials were a definitive break at that specific point in time from the ones that had immediately preceded them, especially in bringing to the fore the bahu (daughter-in-law) of Hindu urban extended families. It traces the complex place of gender in the discourse of the Hindu right and explores the strong debt that the K-serials owe to the ideological constructions of the woman and the family by Hindu nationalism. It argues therefore that the consequences of celebrating agency and empowerment in a right wing milieu-as some recent scholarship has done-ends up advocating for a limited and exclusionary form of female agency.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé

Tears, Talk, and Play: A Window to Gender and Sexuality on Tamil Television - Vangal, Uma (Channeling Cultures: Television Studies from India, 2014)
Tamil television lends itself to some interesting initiatives in gender empowerment through its programming in 3 categories – fiction, reality, and talent shows. This chapter provides a glimpse into television programmes on leading Tamil channels over the last decade (2000–10) from a gender perspective. Focusing particularly on women and transgender characters/hosts, emotional and psychological quotients of the shows and their audiences, moments of dramatic intensity, the chapter demonstrates how the vernacular televisual representations were quite different from the stereotypical portrayals of the mainstream ‘national’ television, even though the programmes were produced, televised, and received within the broader patriarchal framework of Tamil cultural and political contexts. The chapter, as a whole, intends to look at the production, representation and identification of Tamil television soaps and reality shows as vehicle for spotlighting gender issues and alternative sexualities in the public domain.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé